PERAN SEKSUAL DAN NEGOSIASI KONDOM OLEH LAKI SEKS LAKI DI KABUPATEN BULELENG, BALI: Array (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2019)
Introduction: The epicentrum of HIV / AIDS the highest in the man sex with man(MSM) followed by female sex workers (FSW). The MSM community is a community that has not yet been opened and is difficult to intervene them. Low condom use and higher MSM estimates are one of the reported increases in HIV / AIDS. Goals: the goal to identified of a sexual role, characteristic of MSM, and also discusses MSM negotiation techniques for both old and new couples. Method: this research is a quantitative study with cross sectional research taken at MSM services at Buleleng Health Center 1. The samples taken were 58 respondents with interview techniques through questionnaires, negotiations and condom use. The analysis used was univariate, bivariate and multivariate are carried out with logistic regression using software. Results: The results of this study found that the most heterosexual role was 43.1%. Effective negotiation is carried out on new partners is the risk information (AOR: 7.2 95% CI 1.2-40.3) and on old couples by direct request (AOR: 2.3 95% CI 0.2-227,9). Conclusion: condom negotiation by MSM is still very low and based on the type of partner. The new partner is more effective in the delivery of profitable information techniques while the old partner is more effective by asking directly.